A short history of the Weimar Republic - Storer, Colin (I.B. Tauris short histories., 2013)
It is impossible to understand the history of modern Europe without some knowledge of the Weimar Republic. The fourteen-year period of democracy was marked by unstable government, economic crisis and the rise of extremist politics. Yet at the same time a vibrant cultural scene flourished, which continues to influence the international art world.